Perotrochus caledonicus (Gastropoda: Pleurotomariidae) revisited: descriptions of new species from the South-West Pacific - Patrick Anseeuw; Nicolas Puillandre; José Utge; Philippe Bouchet (European Journal of Taxonomy, 2015)
Morphological (shell) and molecular examination of a large suite of specimens of pleurotomariids from around New Caledonia and the Coral Sea reveals the existence of four species in the complex of Perotrochus caledonicus: Perotrochus deforgesi Métivier, 1990 and P. pseudogranulosus sp. nov. live allopatrically on the plateaus and guyots of the Coral Sea; Perotrochus caledonicus Bouchet & Métivier, 1982 and Perotrochus wareni sp. nov. live sympatrically - but essentially not syntopically - on the slopes of New Caledonia, Norfolk Ridge and the Loyalty Ridge. All species live in the 300–500 m interval, and together form a significant component of the mollusc fauna living on hard bottoms in the SW Pacific, with individual dredge hauls containing up to 25 specimens of Perotrochus.